Emerging Environmental, Social, and Governance Funding for Malaysian Micro, Small, and Medium Enterprises - Hock, Ong Joo; Khatibi, Ali; Mohd Talib, Zunirah; George, Roshni Ann (Journal of Information Systems Research and Practice, 2024)
The adoption of Environmental, Social, and Governance practices by Micro, Small, and Medium Enterprises is challenging on several levels, particularly due to financial constraints. With the onset of the digital age, technology driven funding mechanisms are paving the way for new funding pathways that are more accessible to financially constrained enterprises. As these new mechanisms are still in an early developmental phase in Malaysia, it remains uncertain how important they are in fostering Environmental, Social, and Governance practices among Micro, Small, and Medium Enterprises. Therefore, this study examines emerging Environmental, Social, and Governance funding mechanisms, such as micro-financing and crowdfunding, for Micro, Small, and Medium Enterprise in Malaysia. Surveys, interviews, and document analyses were used to investigate the role these funding mechanisms have in advancing Environmental, Social, and Governance among Malaysian Micro, Small, and Medium Enterprises. Institutional theory, employed to analyse the findings, emphasises the importance of institutional mechanisms in the development of emerging funding for Environmental, Social, and Governance. The future development of emerging funding pathways and their impact on Environmental, Social, and Governance adoption among Malaysian Micro, Small, and Medium Enterprises will depend heavily on the interplay of key institutions at the national level.